Selenium-Based Multithreading Functional Testing - Khabib Mustofa; Sunu Pinasthika Fajar (IJCCS (Indonesian Journal of Computing and Cybernetics Systems), 2018)
In a software development projects, testing is an activity that can spend time, effort or cost up to 35%. To reduce this, developers can choose automatic testing. Automated testing, especially for functional testing, on web applications can be done by using tools, one of which is Selenium. By default, Selenium testing is done sequentially and without exploiting multithreading, which has an impact a sufficiently long time.In this study, a platform that allows Selenium users to test and utilize multithreading with Ruby language to speed up testing was developed. Thr result shows that Ruby's multithreading has proven to be capable of speeding functional testing up on various web applications. Variations occur depending on the functionality being tested, the testing approach and also the type of browsers used.